Code Mixing Analysis of Puella ID's Guest Stars on YouTube Channel - Rey Yuditha Aninda (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This study discusses the use of code-mixing by guest stars who are invited to appear and chat with the presenters on a YouTube Channel called Puella ID. This study discusses the types, functions and patterns of code-mixing spoken by the guest stars. In analyzing, this study uses the theory proposed by Muysken for the types and patterns used. As for functions, this study uses the theory proposed by Hoffman. To carry out the research, seven guest stars from different videos are used as the objects. This study uses the qualitative method. The result of this study indicate that there are 3 types and 4 functions of code-mixing from the data. The results of this study are expected to be used as a guide in understanding the varieties of types, functions and patterns of code-mixing spoken by speakers.